Asymmetric Dearomatization of Indole Derivatives with N‐Hydroxycarbamates Enabled by Photoredox Catalysis. (24th October 2019) - Cheng, Yuan‐Zheng; Zhao, Qing‐Ru; Zhang, Xiao; You, Shu‐Li
Abstract: Dearomatization of indoles provides efficient synthetic routes for substituted indolines. In most cases, indoles serve as nucleophiles. Reported here is an asymmetric dearomatization reaction of indole derivatives that function as electrophiles. The combination of a photocatalyst and chiral phosphoric acid open to air unlocks the umpolung reactivity of indoles, enabling their dearomatization with N ‐hydroxycarbamates as nucleophiles. A variety of fused indolines bearing intriguing oxy‐amines were constructed in excellent yields with moderate to high enantioselectivities. Mechanistic studies show that the realization of two sequential single‐electron transfer oxidations of the indole derivatives is key, generating the configurationally biased carbocation species while providing the source of stereochemical induction. These results not only provide an efficient synthesis of enantioenriched indoline derivatives, but also offer a novel strategy for further designing asymmetric dearomatization reactions. Abstract : Die Dearomatisierung von Indolen bietet einen effizienten Zugang zu substituierten Indolinen. Durch die kombinierte Verwendung eines Photokatalysators und einer chiralen Phosphorsäure unter Umgebungsbedingungen wird die Umpolungsreaktivität der Indole aktiviert und ihre enantioselektive Dearomatisierung mit N ‐Hydroxycarbamaten als Nukleophile erreicht.